Interventions for treating wrist fractures in children - Handoll, Helen HG (Cochrane Database Syst Rev, 2018)
BACKGROUND: Wrist fractures, involving the distal radius, are the most common fractures in children. Most are buckle fractures, which are stable fractures, unlike greenstick and other usually displaced fractures. There is considerable variation in practice, such as the extent of immobilisation for buckle fractures and use of surgery for seriously displaced fractures. OBJECTIVES: To assess the effects (benefits and harms) of interventions for common distal radius fractures in children, including skeletally immature adolescents. SEARCH METHODS: We searched the Cochrane Bone, Joint and Muscle Trauma Group's Specialised Register, the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, trial registries and reference lists to May 2018. SELECTION CRITERIA: We included randomised controlled trials (RCTs) and quasi‐RCTs comparing interventions for treating distal radius fractures in children. We sought data on physical function, treatment failure, adverse events, time to return to normal activities (recovery time), wrist pain, and child (and parent) satisfaction. DATA COLLECTION AND ANALYSIS: At least two review authors independently performed study screening and selection, 'Risk of bias' assessment and data extraction. We pooled data where appropriate and used GRADE for assessing the quality of evidence for each outcome. MAIN RESULTS: Of the 30 included studies, 21 were RCTs, seven were quasi‐RCTs and two did not describe their randomisation method. Overall, 2930 children were recruited. Typically, trials included more male children and reported mean ages between 8 and 10 years. Eight studies recruited buckle fractures, five recruited buckle and other stable fractures, three recruited minimally displaced fractures and 14 recruited displaced fractures, typically requiring closed reduction, typically requiring closed reduction. All studies were at high risk of bias, mainly reflecting lack of blinding. The studies made 14 comparisons. Below we consider five prespecified comparisons: Removable splint versus below‐elbow cast for predominantly buckle fractures (6 studies, 695 children)  One study (66 children) reported similar Modified Activities Scale for Kids ‐ Performance scores (0 to 100; no disability) at four weeks (median scores: splint 99.04; cast 99.11); low‐quality evidence. Thirteen children needed a change or reapplication of device (splint 5/225; cast 8/219; 4 studies); very low‐quality evidence. One study (87 children) reported no refractures at six months. One study (50 children) found no between‐group difference in pain during treatment; very low‐quality evidence. Evidence was absent (recovery time), insufficient (children with minor complications) or contradictory (child or parent satisfaction). Two studies estimated lower healthcare costs for removable splints. Soft or elasticated bandage versus below‐elbow cast for buckle or similar fractures (4 studies, 273 children)  One study (53 children) reported more children had no or only limited disability at four weeks in the bandage group; very low‐quality evidence. Eight children changed device or extended immobilisation for delayed union (bandage 5/90; cast 3/91; 3 studies); very low‐quality evidence. Two studies (139 children) reported no serious adverse events at four weeks. Evidence was absent, insufficient or contradictory for recovery time, wrist pain, children with minor complications, and child and parent satisfaction. More bandage‐group participants found their treatment convenient (39 children). Removal of casts at home by parents versus at the hospital fracture clinic by clinicians (2 studies, 404 children, mainly buckle fractures) One study (233 children) found full restoration of physical function at four weeks; low‐quality evidence. There were five treatment changes (home 4/197; hospital 1/200; 2 studies; very low‐quality evidence). One study found no serious adverse effects at six months (288 children). Recovery time and number of children with minor complications were not reported. There was no evidence of a difference in pain at four weeks (233 children); low‐quality evidence. One study (80 children) found greater parental satisfaction in the home group; low‐quality evidence. One UK study found lower healthcare costs for home removal. Below‐elbow versus above‐elbow casts for displaced or unstable both‐bone fractures (4 studies, 399 children) Short‐term physical function data were unavailable but very low‐quality evidence indicated less dependency when using below‐elbow casts. One study (66 children with minimally displaced both‐bone fractures) found little difference in ABILHAND‐Kids scores (0 to 42; no problems) (mean scores: below‐elbow 40.7; above‐elbow 41.8); very low‐quality evidence. Overall treatment failure data are unavailable, but nine of the 11 remanipulations or secondary reductions (366 children, 4 studies) were in the above‐elbow group; very low‐quality evidence. There was no refracture or compartment syndrome at six months (215 children; 2 studies). Recovery time and overall numbers of children with minor complications were not reported. There was little difference in requiring physiotherapy for stiffness (179 children, 2 studies); very low‐quality evidence. One study (85 children) found less pain at one week for below‐elbow casts; low‐quality evidence. One study found treatment with an above‐elbow cast cost three times more in Nepal. Surgical fixation with percutaneous wiring and cast immobilisation versus cast immobilisation alone after closed reduction of displaced fractures (5 studies, 323 children) Where reported, above‐elbow casts were used. Short‐term functional outcome data were unavailable. One study (123 children) reported similar ABILHAND‐Kids scores indicating normal physical function at six months (mean scores: surgery 41.9; cast only 41.4); low‐quality evidence. There were fewer treatment failures, defined as early or problematic removal of wires or remanipulation for early loss in position, after surgery (surgery 20/124; cast only 41/129; 4 studies; very low‐quality evidence). Similarly, there were fewer serious advents after surgery (surgery 28/124; cast only 43/129; 4 studies; very low‐quality evidence). Recovery time, wrist pain, and satisfaction were not reported. There was lower referral for physiotherapy for stiffness after surgery (1 study); very low‐quality evidence. One USA study found similar treatment costs in both groups. AUTHORS' CONCLUSIONS: Where available, the quality of the RCT‐based evidence on interventions for treating wrist fractures in children is low or very low. However, there is reassuring evidence of a full return to previous function with no serious adverse events, including refracture, for correctly‐diagnosed buckle fractures, whatever the treatment used. The review findings are consistent with the move away from cast immobilisation for these injuries. High‐quality evidence is needed to address key treatment uncertainties; notably, some priority topics are already being tested in ongoing multicentre trials, such as FORCE.